The association between cruciferous vegetable consumption and Perfluorooctanesulfonic acid bioaccumulation: A cross-sectional analysis of the US population and cross-country randomized clinical trial validation - Xiaobing Zhai; Junjun Ji; Jing Wang; Jinji Bai; Xuechen Zhao; Wenjie Zhang; Ruyan Lv; Xuan Deng; Qixiu Li; Weiyu Meng; Qianqian Zhang; Jinyuan Zhao; et al. (Environmental Chemistry and Ecotoxicology)
Perfluorooctanesulfonic acid (PFOS) poses significant health risks from bioaccumulation in humans. Effective strategies for removing bioaccumulated PFOS are limited. This study systematically investigated the association between PFOS reduction and cruciferous vegetable intake through a cross-section analysis of 2258 NHANES participants, followed by a 14-day randomized clinical trial (RCT) validation (n = 38). Plasma lipidomics and reverse docking explored the metabolic changes and potential targets related to PFOS elimination from broccoli intake. In NHANES, frequent cruciferous intake was associated with lower odds of high serum PFOS (OR and 95 % CI: 0.63 [0.41–0.96] after adjustment of all known covariates). The RCT demonstrated a significant decrease in serum PFOS after broccoli-orange juice intervention (median reduction = 5.9 %, P = 0.003), but not after orange juice alone (median reduction = 0.3 %, P = 0.153). Lipdiomics revealed PFOS-reduction related changes in steroid, ganglioside, ceramide metabolism and the urea cycle. Target fishing identified strong binding between the pregnane X receptor (PXR), a regulator of steroid/xenobiotic metabolism, and broccoli bioactives including glucoraphanin and sulforaphane. Overall, these findings have significant implications for developing dietary strategies to mitigate PFOS health risks.